PENGEMBANGAN LAS MATEMATIKA BERBASIS AKTIVITAS KREATIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - M.Pd, Suriyani (IKIP Siliwangi, 2018)
The focus of this research is to develop learning instruments in the form of LAS based on creative activities to be used in classroom learning and analyze the relationship between the use of LAS in improving students' creative thinking abilities. The type of research used is development research (research & development). The population of this study were all students of Class VIII and IX of MTs Negeri Rantauprapat in the 2017/2018 Learning Year through purposive sampling technique. The instrument used consisted of LAS Validity Sheet and Activity Questionnaire Sheet and Creative Thinking Ability Test. The data obtained in this study will be analyzed for its reliability and analyzed the relationship between the use of LAS in learning and the improvement of students' creative thinking skills. Validation analysis of the questions was in a valid category with an index of tcount> tTable that was 4.426> 2.04; from the aspect of reliability, the index r11 = 0.53 is obtained, namely the medium category; The difference between questions has an average index of 0.365 which is good, and the difficulty level of the questions has a diverse index so that the questions presented are good enough and suitable for use in learning in schools that want to prioritize students' creative activities. Based on the results of the analysis of the average difference between students 'creative thinking skills before and after using creative based LAS, it was found that the improvement of students' creative thinking ability increased significantly by looking at the Gain index before and after using LAS of 3.157.